Intestinal malabsorption in cystic fibrosis. - Penny, D J (1986)
An oral solution containing lactulose and L-rhamnose was administered to six patients with cystic fibrosis. Intestinal absorption of both sugars was assessed by measurement of their urinary excretion. The lactulose: L-rhamnose excretion ratio was raised, supporting the hypothesis of an intestinal component to the malabsorption of cystic fibrosis.